A Transtextual Hermeneutic Journey: Horst Rosenthal's Mickey au camp de Gurs (1942). Issue 1 (1st June 2019) - Sacerdoti, Yaakova
Abstract : Gérard Genette's transtextuality theory serves as the basis for a hermeneutic inquiry into Horst Rosenthal's Mickey au camp de Gurs. Multiple levels of meaning emerge from transtextual links to other literary genres and works of Western culture, from Disney's early animations to fairy tales and satire, concluding with Dante's Inferno. This article analyses Rosenthal's transtextual discourse and shows how his use of the comic genre to depict the horrors of the Gurs internment camp involves readers in what happened there and produces a text that speaks to all. Using Mickey Mouse, the international cartoon hero, alongside referencing the Inferno, a cornerstone of the Western canon, turns Rosenthal's experience into a universal one and permits author and reader to focus on the emotional level that transcends all rationality.